Do markets prove pessimists right? - Eichberger, Jürgen; Guerdjikova, Ani Vladimirova (International economic review, 2018)
We study how ambiguity and ambiguity attitudes affect asset prices when consumers form their expectations based on past observations. In an overlapping generations economy with risk-neutral yet ambiguity-sensitive consumers, we describe limiting asset prices depending on the proportion of investor types. We then study the evolution of consumer-type shares. With long memory, the market does not select for ambiguity neutrality. Whenever perceived ambiguity is sufficiently small, but positive, only pessimists survive and determine prices in the limit. With one-period memory, equilibrium prices are determined by Bayesians. Yet, the average price of the risky asset is lower than its fundamental value.
Gesehen am 30.07.2018